Procedimientos para realizar seguimiento a las rutas de atención en salud implementadas en el municipio de San Bernardo del Viento (2023)
Resolution 3280 of 2018, which adopts the technical and operational guidelines of the comprehensive care route for the promotion and maintenance of health, as well as the guidelines for its implementation, marks a new beginning for the comprehensive care of users in the different life courses and specific health protection activities. The health care routes are a fundamental tool, which organizes the necessary management to carry out the care, its main reason is to improve the living conditions of the users and promote compliance with the actions and interventions that guarantee the fundamental right to health. The objective of this work is to design the procedures to monitor the health care routes in the municipal Health Secretariat in San Bernardo del Viento. In the methodology of this proposal, a descriptive study will be carried out because the procedures will be designed to monitor the health care routes implemented in the municipality, therefore, during the development of business practices carried out in the Secretariat. of Municipal Health in the area of Public Health I hope to acquire a great knowledge about the processes executed in this unit, based on the detected need, reviewing compliance with the necessary standards to guarantee the quality of health services.